Cross-cultural effects on detecting multiple sources of driving hazard: Evidence from the deceleration detection flicker test. (February 2020) - Lee, Yee Mun; Miller, Karl; Crundall, David; Sheppard, Elizabeth
Highlights: Effects of experience/culture on Deceleration Detection Flicker Task were tested. Malaysian and UK drivers detected lead vehicle deceleration and secondary hazards. Malaysian drivers were poorer at detecting deceleration and hazards. Experienced drivers performed better across cultures. The DDFT could be used as a training tool for Malaysian drivers. Abstract: Collision rates in Malaysia are much higher than the UK; do these reflect poorer hazard perception skill or does exposure to hazardous events improve hazard detection ability? The deceleration detection flicker test (DDFT) was used to investigate the effect of experience and cross-cultural differences between Malaysian and UK drivers in their ability to detect the deceleration of a lead vehicle while simultaneously identifying any secondary hazards in side roads. Matched groups of participants with lower or higher levels of experience were recruited from the University of Nottingham in the UK and Malaysia. Malaysian drivers were significantly less accurate than UK drivers in detecting the deceleration of lead vehicles on urban roads, and significantly less accurate in detecting the presence of secondary hazards across all road types. Experienced drivers were significantly faster than novices in detecting decelerations of the lead vehicle, and were significantly more accurate in detecting the presence of secondary hazards. The study concludes that high exposure to hazardous events on the road in Malaysia does not yield expertise in this hazard perception task, although the DDFT does differentiate experience cross-culturally.